The Effect of Implementing Sharia Principles in the Financial Industry on Economic Stability: Case Study at Bank BTPN Syariah - Tama Putra Saratian, Eko; Rokhmatul Aysa, Imma; Sudiana, Urip (Al Urwah : Sharia Economics Journal, 2024)
This study investigates the impact of implementing Sharia principles on economic stability, using Bank BTPN Syariah as a case study. By adhering to core Islamic financial tenets such as the prohibition of interest (riba), the avoidance of excessive uncertainty (gharar), and the emphasis on risk-sharing and asset-backed financing, Bank BTPN Syariah aims to foster a more resilient and ethical financial system. Data was collected through interviews with key stakeholders, surveys of clients, and analysis of financial documents. The findings indicate that the application of Sharia principles contributes significantly to financial stability by promoting prudent risk management and ethical investment practices. The bank's focus on financial inclusion and supporting underserved communities enhances economic stability and client trust. This study reinforces existing theoretical frameworks that highlight the benefits of Islamic banking in mitigating financial risks and promoting sustainable economic growth. Practical implications for Bank BTPN Syariah include maintaining strong regulatory compliance and enhancing ethical conduct, while broader recommendations for the Islamic banking sector and policymakers emphasize the need for supportive frameworks to facilitate the widespread adoption of Sharia principles. Future research should explore the long-term impacts of Sharia-compliant practices and the role of technological advancements in this sector.